EPEN-09. PRECLINICAL MODELS REVEAL SUBGROUP-STRATIFIED TARGETED THERAPY OPTIONS FOR CHILDHOOD SUPRATENTORIAL EPENDYMOMA. (23rd April 2019) - Amani, Vladimir; Donson, Andrew; Griesinger, Andrea; Witt, Davis; Levy, Jean Mulcahy; Hoffman, Lindsey; Hankinson, Todd; Handler, Michael; Vibhakar, Rajeev; Dorris, Kathleen; Foreman, Nicholas
Abstract: Treatment of ependymoma has changed little over the years and is essentially limited to surgery and radiation. Limited preclinical testing has hindered the development of targeted therapies. Our group has identified a variety of potential therapy options for ependymoma based on drug screening using novel human posterior fossa ependymoma cell lines with chromosome 1q gain. Whether these agents were also effective in RELA fusion-driven supratentorial ependymoma was not determined due to of a lack of available supratentorial ependymoma cell lines. Recently we were able to generate a novel supratentorial cell line – MAF1329 - harboring 1q+ as well as the RELA-C11orf95 fusion. Paired with a supratentorial ependymoma cell line (EP1NS) obtained from collaborators, we were able to perform an in vitro screen and to identify supratentorial ependymoma-selective therapies in a panel of 124 FDA-approved oncology drugs, for streamlined clinical application. Additionally, we are able to compare drug sensitivities between supratentorial and posterior fossa ependymoma. Our initial findings indicate that the two ependymoma subgroups differ in response to therapy options with some overlap, notably RTKIs imatinib and pazopanib. We also noted that carmofur, a lypophilic-masked analog of 5-FU, was effective in treating both subgroups. Conversely, 5-FU itself, a top hit in posterior fossa ependymoma, showed very little effect in supratentorial models. Early phase trials of 5-FU resulted in a lack of survival benefit in supratentorial tumors enrolled in the study, and this preclinical finding may explain this lack of response. These data suggest that supratentorial and posterior fossa ependymoma may require subgroup specific targeted therapy options. Further comparative drug screening of other supratentorial cell lines and short term cultures, combined with in vivo testing, will address the need for subgroup-stratified preclinical data to better inform design of clinical trials in ependymoma.